POLYCATIONIC DOPING OF THE LATP CERAMIC ELECTROLYTE FOR LI-ION BATTERIES - Mashekova, Aiym; Baltash, Yelnury; Yegamkulov, Mukagali; Trussov, Ivan; Bakenov, Zhumabay; Mukanova, Aliya (RSC Advances, 2022)
All-solid-state Li-ion batteries (LIBs) with a solid electrolyte instead of a liquid one demonstrate significantly higher safety in contrast with the conventional liquid-based LIBs. An inorganic NASICON-type Li conductor Li1.3Al0.3Ti1.7(PO4)3 (LATP) is a promising solid electrolyte with an ionic conductivity of up to 10−3 S cm−1 at room temperature. However, LATP gradually degrades in contact with Li metal because of reduction of Ti4+ to Ti3+, resulting in a lower ionic conductivity at the electrolyte–electrode interface. Cation doping is a promising approach to stabilize the LATP structure and mitigate the Ti reduction. Here, we report our findings on the alternative polycationic doping strategy of the LiTi2(PO4)3 (LTP) structure, when a heterovalent cation is added along with Al. In particular, we studied the effect of tetravalent and divalent cation dopants (Zr, Hf, Ca, Mg, Sr) of LATP on the Li-ion conduction and Ti reduction during interaction with lithium metal. The samples were prepared by molten flux and solid-state reaction methods. The structure, morphology, and ion-transport properties of the samples were analyzed. The activation energy of Li-ion migration in all synthesized systems was calculated based on the electrochemical impedance spectroscopy (EIS) data retrieved for a temperature range of 25–100 °C. From the obtained results, the tetravalent doping (Zr4+ and Hf4+) appeared to be a more promissing route to improve the LATP electrolyte than the divalent doping (Mg2+, Ca2+, and Sr2+). The X-ray photoelectron spectroscopy analysis of the samples after their contact with lithium provided the data, which could shed light on the effect of the incorporated dopants onto the Ti reduction.
Keywords: Type of access: Open Access; LATP ceramic electrolyte; Li-ion batteries